Responses of Tropical Background State and ENSO Behaviors to Mid-Holocene Forcing Simulated by PMIP3 and PMIP4 Models - Song, Meng-Er; Chen, Lin (Frontiers in Earth Science, 2022)
Abstract The mid-Holocene (MH), a period about 6000 years ago, provides an opportunity to understand climate change in response to orbital forcing change. Numerical model simulation is an effective tool through which we can study the climate change in the MH, although the climate in the MH can be partly inferred from proxy data. As the Paleoclimate Model Inter-comparison Project Phase 4 (PMIP4) recently released the latest simulations for different past climate scenarios, we investigated tropical climate changes, including both the basic state and interannual variability, and tried to find out whether the PMIP Phase3 (PMIP3) and PMIP4 results can be reconciled. Almost all the modelling results show that the inter-hemisphere contrast was enhanced over the tropical Pacific, with warmer and wetter condition on the northern side of the equator and an intensified cross-equatorial flow in the MH than at present, and the annual cycle of the sea-surface temperature (SST) during the MH was reduced. Such background mean state changes arose from the seasonal changes of the solar incident radiation in the MH. In addition to the consistent changes in background mean state changes, some El Nino-Southern Oscillation (ENSO) features, such as the seasonal phase locking feature and periodicity, show consistent changes across the PMIP3 and PMIP4 models, that is, both suites of models exhibit no marked difference in the MH with respect to present-day simulations. In contrast, the modeling results show only agreement on the sign of the ENSO amplitude change, (i.e., decrease in the ENSO amplitude in the MH), while the range of reduction varied with model and region. Additionally, the occurrence probability of central Pacific El Nino events increases in the MH, whereas the signiﬁcance is quite marginal. The modeled changes in the mean state and ENSO serve as a test bed for studying tropical climate system’s response to natural warming, which may provide some insights into understanding climate changes in response to the current anthropogenic warming.